(3TQM CdaGX GdaUjMs - (3YHO Gddg Hf YHO GdQMje GdCUagGfjs; (3CHh GSMGb CMeO Hf eMeO Hf EHQGgje GdfjSCHhQj, GdKYdHj,J (B427 (3g` s
(3ChdgG (B:s
(3jHOC HHGH aYdJ HaJM GdYjf s
(3BNQgG (B:s
(3jfJgi HHGH ef GdaQb s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B212s
Keywords: (3GddZIs